Granulomatous prostatitis after intravesical immunotherapy mimicking prostate cancer - Waldemar Białek; Sławomir Rudzki; Paweł Iberszer; Lech Wronecki (Journal of Ultrasonography, 2016)
Intravesical immunotherapy with attenuated strains of Mycobacterium bovis is a widely used therapeutic option in patients with non-muscle-invasive transitional cell carcinoma of the bladder. A rare complication of intravesical therapy with the Bacillus Calmette-Guérin vaccine is granulomatous prostatitis, which due to increasing levels of prostate-specific antigen and abnormalities found in transrectal examination of the prostate may suggest concomitant prostate cancer. A case of extensive granulomatous prostatitis in a 61-year-old patient which occurred after the first course of a well-tolerated Bacillus Calmette-Guérin therapy is presented. Due to abnormalities found in rectal examination and an abnormal transrectal ultrasound image of the prostate with extensive infiltration mimicking neoplastic hyperplasia a core biopsy of the prostate was performed. Histopathological examination revealed inflammatory infiltration sites of tuberculosis origin.